Multimorbidity and chronic diseases among undocumented migrants: evidence to contradict the myths - Luis Andrés Gimeno-Feliu; Marta Pastor-Sanz; Beatriz Poblador-Plou; Amaia Calderón-Larrañaga; Esperanza Díaz; Alexandra Prados-Torres (BMC, 2020)
Abstract Background There is little verified information on the global health status of undocumented migrants (UMs). Our aim is to compare the prevalence of the main chronic diseases and of multimorbidity in undocumented migrants, documented migrants, and Spanish nationals in a Spanish autonomous community. Methods Retrospective observational study of all users of the public health system of the region of Aragon over 1 year (2011): 930,131 Spanish nationals; 123,432 documented migrants (DMs); and 17,152 UMs. Binary logistic regression was performed to examine the association between migrant status (Spanish nationals versus DMs and UMs) and both multimorbidity and individual chronic diseases, adjusting for age and sex. Results The prevalence of individual chronic diseases in UMs was lower than in DMs and much lower than in Spanish nationals. Comparison with the corresponding group of Spanish nationals revealed odds ratios (OR) of 0.1-0.3 and 0.3-0.5 for male and female UMs, respectively (p < 0.05 in all cases). The risk of multimorbidity was lower for UMs than DMs, both for men (OR, 0.12; 95%CI 0.11-0.13 versus OR, 0.53; 95%CI 0.51-0.54) and women (OR, 0.18; 95%CI 0.16-0.20 versus OR, 0.74; 95%CI 0.72-0.75). Conclusions Analysis of data from a health system that offers universal coverage to all immigrants, irrespective of legal status, reveals that the prevalence of chronic disease and multimorbidity is lower in UMs as compared with both DMs and Spanish nationals. These findings refute previous claims that the morbidity burden in UM populations is higher than that of the native population of the host country.